Design and simulation of CsPb.625Zn.375IBr2-based perovskite solar cells with different charge transport layers for efficiency enhancement - M. Khalid Hossain; Md Aminul Islam; M. Shihab Uddin; Prabhu Paramasivam; Junainah Abd Hamid; Razan A. Alshgari; V. K. Mishra; Rajesh Haldhar (Scientific Reports)
Abstract In this work, CsPb.625Zn.375IBr2-based perovskite solar cells (PSCs) are numerically simulated and optimized under ideal lighting conditions using the SCAPS-1D simulator. We investigate how various hole transport layers (HTL) including Zn3P2, PTAA, MoS2, MoO3, MEH-PPV, GaAs, CuAlO2, Cu2Te, ZnTe, MoTe2, CMTS, CNTS, CZTS, CZTSe and electron transport layers (ETL) such as CdS, SnS2, ZnSe, PC60BM interact with the devices’ functionality. Following HTL material optimization, a maximum power conversion efficiency (PCE) of 16.59% was observed for the FTO/SnS2/CsPb.625Zn.375IBr2/MoS2/Au structure, with MoS2 proving to be a more economical option. The remainder of the investigation is done following the HTL optimization. We study how the performance of the PSC is affected by varying the materials of the ETL and to improve the PCE of the device, we finally optimized the thickness, charge carrier densities, and defect densities of the absorber, ETL, and HTL. In the end, the optimized arrangement produced a VOC of 0.583 V, a JSC of 43.95 mA/cm2, an FF of 82.17%, and a PCE of 21.05% for the FTO/ZnSe/CsPb.625Zn.375IBr2/MoS2/Au structure. We also examine the effects of temperature, shunt resistance, series resistance, generation rate, recombination rate, current-voltage (JV) curve, and quantum efficiency (QE) properties to learn more about the performance of the optimized device. At 300 K, the optimized device provides the highest thermal stability. Our research shows the promise of CsPb.625Zn.375IBr2-based PSCs and offers insightful information for further development and improvement.